ANALISIS PENDAPATAN UMKM ONLINE MAHASISWA SEBELUM DAN SETELAH TERKENA DAMPAK PANDEMI COVID-19 - Pandjisiswoutomo, Natsir Abdulkarim; Ashar, Khusnul (Contemporary Studies in Economic, Finance and Banking, 2022)
The outbreak of COVID-19 in Indonesia since the early of 2020 has resulted in many negative effects, particularly in the economic sector. Small and Medium Enterprise (SME, UMKM in Indonesia) is one of the economic sector that most affected by this condition. Social distancing that applied during the outbreak has affected the people’s tendency to shop without ignoring that policy by shopping through the technology of e-commerce. This, of course has the effect on the increasing of the number of access on various shopping service platforms. Based on a survey of We Are Social in April 2021, in the last few months 88, 1% of web users in Indonesia use the e-commerce services for buying certain product. Based on that fact, this research is conducted with the aim of finding out whether there was a change in the income of SME managed by university students in Malang City before and during the effects of COVID-19 pandemic. This research is quantitative research and uses paired sample t-test method to test the data obtained through the questionnaire method. The result of this research shows that there was a change in the amount of income of online based SME managed by university students in Malang City before and after the effects of COVID-19 pandemic, with 65% of the total respondents experience an increase in income, 29% of the total respondents experience a decreasing in income, and the other 3% did not experience any change.